Investment in Education in Nigeria: Barriers and Way Forward - OGUNODE, Niyi Jacob; G,. E., ATTAH,; J., EBUTE, (Journal of Higher Education and Academic Advancement, 2024)
This paper discussed barriers to investment in education in Nigeria. Secondary data were used in the paper. The secondary data were gathered from print materials and online publications. The paper identified the poor implementation of national policy on funding of education, subsidy payment, debt servicing, corruption, insecurity problems, fall in national revenue and revenue loss as barriers to investment in education in Nigeria. Based on these problems identified, the paper hereby recommended that government at every tier should implement the National Policy on education financing in Nigeria. The government should remove the subsidy and reinvest the funds in education, health and other sector. The government should reduce the rate at which they are going for both foreign and local loans to reduce the debt rate of Nigeria. The government should employ anti-corruption legal and regulatory instruments to fight corruption in the education sector. Government should improve the finance and accounts systems in the Ministry of Education to strengthen management and audit to improve accountability at national and district levels.